Rational sentiments and financial frictions - Paymon Khorrami; Fernando Mendo (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2025)
We discover sentiment-driven equilibria in popular models of imperfect risk sharing. In these equilibria, sentiment dynamics behave like uncertainty shocks, in the sense that self-fulfilled beliefs about volatility drive aggregate fluctuations. Because such fluctuations can decouple from the wealth distribution, rational sentiment helps resolve two puzzles plaguing models emphasizing balance sheets: (i) financial crises emerge suddenly, featuring large volatility spikes and asset-price declines; (ii) assetprice booms, with below-average risk premia, predict busts and financial crises. Methodologically, our contribution is using stochastic stability theory to establish existence of sunspot equilibria.
Keywords: E00; E44; G01; 330; financial frictions; sunspot equilibria; self-fulfilling beliefs; sentiment; financial crises; uncertainty shocks